Nation-Wide Viral Sequence Analysis of HIV-1 Subtype B Epidemic in 2003–2012 Revealed a Contribution of Men Who Have Sex With Men to the Transmission Cluster Formation and Growth in Japan - Shiino, Teiichiro; Hachiya, Atsuko; Hattori, Junko; Sugiura, Wataru; Yoshimura, Kazuhisa (Frontiers in Reproductive Health, 2020)
Background To better understand the epidemiology of human immunodeficiency virus type 1 (HIV-1) subtype B transmission in Japan, phylodynamic analysis of viral pol sequences was conducted on individuals newly diagnosed as HIV-1 seropositive. Methodology A total of 5,018 patients newly diagnosed with HIV-1 infection and registered in the Japanese Drug Resistance HIV Surveillance Network from 2003 to 2012 were enrolled in the analysis. Using the protease-reverse transcriptase nucleotide sequences, their subtypes were determined, and phylogenetic relationships among subtype B sequences were inferred using three different methods: distance-matrix, maximum likelihood and Bayesian Markov chain Monte Carlo. Domestically spread transmission clusters (dTCs) were identified based on the following criteria: >95% in interior branch test, >95% in Bayesian posterior probability and <10% in depth-first searches for sub-tree partitions. The association between dTC affiliation and individuals’ demographics was analyzed using univariate and multivariate analyses. Results Among the cases enrolled in the analysis, 4,398 (87.6%) were classified as subtype B. Many of them were Japanese men who had sex with men (MSM), and 3,708 (84.3%) belonged to any of 312 dTCs. Among these dTCs, 243 (77.9%) were small clusters with <10 individuals, and the largest cluster consisted of 256 individuals. Most dTCs had median time of the most recent common ancestor between 1995 and 2005, suggesting that subtype B infection was spread among MSMs in the second half of the 1990s. Interestingly, many dTCs occurred within geographical regions. Comparing with singleton cases, TCs included more MSM, young person, and individuals with high CD4+ T-cell count at the first consultation. Furthermore, dTC size was significantly correlated with gender, age, transmission risks, recent diagnosis and relative population size of the region mainly distributed. Conclusions Our study clarified that major key population of HIV-1 subtype B epidemic in Japan is local MSM groups. The study suggests that HIV-1 subtype B spread via episodic introductions into the local MSM groups, some of the viruses spread to multiple regions. Many cases in dTC were diagnosed during the early phase of infection, suggesting their awareness to HIV risks.